PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEBIJAKAN DIVIDEN TERHADAP KINERJA PERUSAHAAN DENGAN UMUR PERUSAHAAN SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI 2019-2021 - Arnitia Rahmatika; Idrianita Anis (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2023)
This study examines the impact of institutional ownership and dividend policy on the financial outcomes of manufacturing businesses trading on the Indonesia Stock Exchange (BEI) from 2019 to 2021, with the impact of company age serving as a control variable. To determine an organization's Return On Assets (ROA), net income is divided by its total assets. The age of a company is calculated by subtracting the current year from the year it was founded; the Institutional Ownership Ratio compares the percentage of shares owned by institutions to the total number of shares outstanding; and the Dividend Payout Ratio (DPR) evaluates dividends paid to shareholders in relation to earnings per share. The 183 companies included in this study were chosen using a stratified random selection technique. This study's results suggest that (1) institutional ownership significantly affects firm performance in a positive way. (2) A dividend plan is excellent for a company's bottom line.